ANALISIS FAKTOR PENGHAMBAT DALAM UPAYA MENINGKATKAN KEMAMPUAN LITERASI MEMBACA PADA SISWA KELAS II DI SEKOLAH DASAR NEGERI 03 BENGKAYANG - Sovia Shinta; Siprianus Jewarut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Qualitative research to provide a broad picture of the factors that hinder students' ability to implement reading literacy. Literacy is the ability to read and write as well as speak, listen, understand and think critically. Reading is the window to the world we can gain a lot of knowledge and insight by reading. To improve the quality of education, reading skills are very important to build from an early age. However, interest in reading, especially among elementary school students, is still low in Indonesia. This is a concern and a challenge that will impact on students' learning outcomes and academic achievement. There are a number of reasons for this, such as lack of support from family and friends, more focus on playing online games or electronic devices, lack of facilities and infrastructure, strong personal interest and motivation, and support from schools themselves. The Indonesian government has made various efforts to increase students' interest in reading. One of them is the implementation of a literacy culture, or the School Literacy Movement.